2015
DOI: 10.2147/amep.s69304
|View full text |Cite
|
Sign up to set email alerts
|

Factors potentially influencing academic performance among medical students

Abstract: BackgroundStudies are needed to examine predictors of success in medical school. The aim of this work is to explore factors that potentially influence excellence of medical students.MethodsThe study was conducted in the Medical Faculty of King Abdulaziz University during October 2012. A self-administered questionnaire was used. Medical students with a grade point average (GPA) ≥4.5 (out of 5) were included and compared to randomly selected medical students with a GPA <4.5, who were available at the time of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 12 publications
8
42
1
16
Order By: Relevance
“…No much difference between their means regarding consumption of caffeinated beverages. This finding agrees with the finding of an earlier study (Al Shawwa et al, 2015) who revealed that factors such as expending time watching television and listening to music had no substantial difference amongst medical students of higher and lower GPA scores. However, distinctions were found in time dedicated to different forms of social networking between the groups which might likely have a substantial difference on the student's achievement.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…No much difference between their means regarding consumption of caffeinated beverages. This finding agrees with the finding of an earlier study (Al Shawwa et al, 2015) who revealed that factors such as expending time watching television and listening to music had no substantial difference amongst medical students of higher and lower GPA scores. However, distinctions were found in time dedicated to different forms of social networking between the groups which might likely have a substantial difference on the student's achievement.…”
Section: Discussionsupporting
confidence: 92%
“…However, their comparative mean scores on each reading style have indicated that pre-clinical students are more likely to engage in mapping, note forming, highlighting, recording, reading aloud and start by memorizing while the clinical students are more likely to employ summarizing, read silently as well as start by reading than memorizing. This discovery is in concord with the results of the previous researchers who observed no significant difference between different reading styles employed by the medical students on their academic performance (Al Shawwa et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations